Efficacy and safety of serplulimab in solid tumors: a meta-analysis - Shen, Peimeng; Zhang, Tao; Hao, Lina; Jing, Ming; Wu, Yanxin; Yu, Shuwen (Frontiers in pharmacology, 2025)
The goal of this study was to investigate the effectiveness and safety of serplulimab in advanced solid tumors through a meta-analysis approach. An electronic search was conducted across the Embase, Web of Science, PubMed, and Cochrane Library databases, covering the period from each database's inception through 6 May 2025. Meta-analysis and related analyses, including subgroup, sensitivity, and publication bias assessments, were performed using Stata 16.0. The Cochrane Risk of Bias Assessment Tool (version 5.1.0) was utilized to measure the quality of randomized controlled trials (RCTs). For single-arm studies, quality was evaluated using the Methodological Index for Non-Randomized Studies (MINORS). Ten studies, including three RCTs and seven single-arm studies, were analyzed, involving 2,020 patients. In the analysis of RCTs, serplulimab significantly elevated overall survival (OS) [HR = 0.68, 95% CI: 0.59-0.79, P < 0.01], disease control rate (DCR) [RR = 1.04, 95% CI: 1.01-1.08, P < 0.05], progression-free survival (PFS) [HR = 0.53, 95% CI: 0.47-0.61, P < 0.01], and objective response rate (ORR) [RR = 1.30, 95% CI: 1.09-1.56, P < 0.01]. The analysis of single-arm studies revealed that the ORR for serplulimab in solid tumors was [ES = 45%, 95% CI: 31%-59%, P < 0.01], and the DCR was [ES = 71%, 95% CI: 63%-80%, P < 0.01]. Among the ten studies, the most common adverse events included reductions in platelet count (0.32, 95% CI: 0.20-0.43), white blood cell count (0.30, 95% CI: 0.17-0.44), anemia (0.29, 95% CI: 0.09-0.48), and proteinuria (0.28, 95% CI: 0.17-0.38). Based on current research, serplulimab appears to be effective for solid tumors. However, given the limitations of the studies, for example, possible selection bias in single-arm studies, further multicenter, high-quality, large-sample RCTs are necessary to validate this conclusion.